MDA Framework Approach for Gamification-Based Elementary Mathematics Learning Design - Syahrizal Dwi Putra; Verdi Yasin (International Journal of Engineering, Science and Information Technology, 2021)
Mathematics is currently one of the compulsory subjects taught in schools and the most difficult subject. By using the MDA Framework approach based on gamification, a visual game of building space was designed. The MDA Framework consists of mechanics, namely certain rules which will then generate dynamics which are the result of the interaction of mechanics with players which will then automatically create aesthetics or player responses. From the design results, it is known that the visual game of building space has followed the stages in the MDA framework and has achieved its goal, namely to provide a learning process about the volume of space building